Microstructural, physical, and thermal analyses of Portland cement-fly ash-calcium hydroxide blended pastes - Nochaiya T. (2014)
The effect of calcium hydroxide (CH) on the properties of Portland-fly ash cement pastes, at up to high-volume fly ash mixes has been investigated using normal consistency, setting time, compressive strength, thermal analysis and scanning electron microscope. CH as an additive material (5 and 10 wt%), lignite fly ash (FA) up to 50 wt% was used to produce Portland cement (PC)-FA-CH pastes at w/PC + FA ratio of 0.5. Water requirement for normal consistency was found to increase with increasing CH content while a decrease in initial setting time was found. Furthermore, the compressive strengths of all FA mixes with CH were found to be higher than the mixes without CH. Thermal analysis and scanning electron microscope were used to study the hydration of PC-FA-CH system. The results showed that the first phase transition detected by thermal analyses was attributed to ettringite, calcium silicate hydrate, gehlenite hydrate and was found to be higher in PC-FA-CH mixes than in pure Portland-FA cement paste resulting in an increase in compressive strength. Moreover, the hydration phases were also found to increase with increasing curing time. Overall, the results show that the additional of 5 wt% CH in Portland-FA mixes especially at high-volume FA mixes was found to accelerate FA pozzolanic reaction at early ages (7 and 28 days), resulting to an increase in compressive strength. © 2009 Akadémiai Kiadó, Budapest, Hungary.